Factors Determining Malaysian Smes Performance in Knowledge Management - Valliappan Raju, Assoc. Prof. Dr.; Siew Poh Phung, Dr.; Sivashankar, Dr. (International Journal of Engineering and Technology, 2019)
The aim of this study involves examining information among corporate and their social capital. A survey technique is employed and the research context involves small and medium-sized enterprises (SMEs). The specific geographical context of the study involves Klang Valley, Malaysia. Indeed, social capital and information have gained interest due to their crucial role in shaping company performance and the realization of any intended goals and objectives. Notably, social capital plays a moderating role in shaping the relationship between the performance of senior executives and company realization of goals. This studyâ€™s findings were obtained from 289 respondents. Major factors under investigation included the expectation of senior executives relative to social capital and how social capital affects organizational performance. Overall, it as established that social capital and information among senior executives yield improvements in organizational performance.Â Â